Innovation in Digital Public Services Through the Sipanduk Application in the Luragung District of Kuningan Regency - Julia Indriyani; Nursahidin Nursahidin (Pelopor Publikasi Akademika, 2026)
SIPANDUK (Population Administration Service Information System) is a public service innovation in the form of an application that is expected to assist the community in Luragung District, Kuningan Regency, in managing population administration online. However, in its implementation, the use of the SIPANDUK application is still not optimal, as indicated by low public interest. This study aims to analyze digital-based public service innovations, the factors causing low public interest in using the SIPANDUK application, and recommendations to increase public participation in using the SIPANDUK application. The analysis of public service innovation is based on the Diffusion of Inno-vation theory by Everett M. Rogers (1962). The research method used is descriptive qualitative with data collection techniques through observation, semi-structured interviews, literature study, and doc-umentation. The results of the study show that digital-based service innovations have not been run-ning optimally. The low level of public interest in Luragung Subdistrict in using the SIPANDUK ap-plication is due to the perception of the complexity of the application, low user needs, preference for face-to-face services, and a lack of digital literacy and socialization. As a result, the SIPANDUK ap-plication has not been fully accepted by the community in Luragung Subdistrict. Therefore, direct socialization, technical assistance, simplification of the application, and optimization of the role of village officials are needed to encourage sustainable use of the application.